2023
DOI: 10.2196/39994
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Drivers of Vaccine Hesitancy During the COVID-19 Pandemic Among Older Adults in Jiangsu Province, China: Cross-sectional Survey

Abstract: Background Older adults are particularly at risk from infectious diseases, including serve complications, hospitalization, and death. Objective This study aimed to explore the drivers of vaccine hesitancy among older adults based on the “3Cs” (confidence, complacency, and convenience) framework, where socioeconomic status and vaccination history played the role of moderators. Methods A cross-sectional questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“… 25 , 26 According to Yang et al, within the context of the “3Cs” framework driving vaccine hesitancy (confidence, complacency, and convenience), confidence played a more significant role in influencing vaccine hesitancy among older adults. 27 Their study identified a positive association between lower socioeconomic status and higher vaccine hesitancy. 27 Vaccine hesitancy in older adults could also be explained by limited access to relevant information or lack of social support.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 25 , 26 According to Yang et al, within the context of the “3Cs” framework driving vaccine hesitancy (confidence, complacency, and convenience), confidence played a more significant role in influencing vaccine hesitancy among older adults. 27 Their study identified a positive association between lower socioeconomic status and higher vaccine hesitancy. 27 Vaccine hesitancy in older adults could also be explained by limited access to relevant information or lack of social support.…”
Section: Discussionmentioning
confidence: 99%
“… 27 Their study identified a positive association between lower socioeconomic status and higher vaccine hesitancy. 27 Vaccine hesitancy in older adults could also be explained by limited access to relevant information or lack of social support. 26 , 28 Utilizing the influence of healthcare professionals in tertiary hospitals could potentially serve as a strategy to mitigate RSV vaccine hesitancy and increase vaccine uptake when RSV vaccines are introduced in China.…”
Section: Discussionmentioning
confidence: 99%
“…This observation is broadly consistent with previous research conducted during different stages of the COVID-19 pandemic. 20 , 58 …”
Section: Discussionmentioning
confidence: 99%